Interpretation of the multifunctional agriculture’s function in regional dimensions - Horváth, Péter (Acta Agraria Debreceniensis, 2012)
Many branches of science have been examining the concept of multifunctional agriculture. Different interpretations have come into being on global and regional dimensions as well. This study deals with certain interpretations of the concept of multifunctional agriculture. It compares the concepts about multifunctional agriculture of the United States, the Cairns-group, the least developed countries (the LDC-s), as well as the developed countries which import food (the G10), the concept of the EU and Hungary too. It states that the different approaches to the concept have been started by the agricultural problems which are typical of certain areas. These problems have been formed in each and every area by the threefold functions (economic, social and ecological), which are characteristics of rural areas.